A review on recent advancement of nano-structured-fiber-based metal-air batteries and future perspective. (December 2020) - Chen, Xiaoqing; Ali, Imdad; Song, Lijian; Song, Peng; Zhang, Youchen; Maria, Semeniuk; Nazmus, Saadat; Yang, Weimin; Dhakal, Hom Nath; Li, Haoyi; Sain, Mohini; Ramakrishna, Seeram
Abstract: In an era of sustainable development and innovation ecosystem, a high-energy density is one of the important requirements for the development of new energy storage modalities, including battery technology. In a metal-air battery (MAB) system, metals function as negative active substances, and oxygen in the air acts as the positive component. Research to date confirms that, MABs have an exceptionally high energy density, durability, and specific power compared to conventional batteries. In addition, they are environmentally friendly, low-cost, and lightweight. In battery construction, fibrous materials have been shown to improve thermal stability, electronic & ionic conductivity, and cyclical performance of MABs. This is due to their outstanding properties that include large surface area-to-volume ratio, controllable morphology and highly porous structure. In this review, the basic working principle of MABs is presented. A critical overview that using a diverse array of fibrous materials related to metal-based, metal oxide-based, and carbon-based fiber shape materials used in MABs such as Li–O2, Zn–O2, Mg–O2, and Al–O2 systems are comprehensively summarized. We also identify the most promising systems according to their established scientific database with respect to sustainable development. Finally, the existing challenges and prospects are stressed considering the future perspective of MABs and fiber-shaped structure electrode material. Graphical abstract: Image 1 Highlights: Carbon-based, metal-based, and metal oxide-based fiber shaped materials for advanced metal-air battery are reviewed. The different synthesis techniques of fiber-shaped material for metal-air battery electrode are presented and emphasized. The relationship between the nanostructure characteristics and performance of the metal-air battery is discussed. The existing challenges and future perspective are suggested.